EVALUASI PELAKSANAAN PROGRAM PENDIDIKAN ANAK USIA DINI DI KECAMATAN TEMBALANG - Saputra, Maulana Yusup; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Education is very important in the process of improving human resources. Because every citizen has the right to obtained a good education. Early childhood education is an effort of constructing, addressed to children from the early birth up to the age of six. Tembalang subdistrict is the area that has the most PAUD and education unit. The research was purposed to evaluate the implementation of the PAUD, Knowing teacher competences, knowing why the PAUD teacher has not academically qualified. The research method that was used is qualitative analysis with data capture techniques namely observation, interviews, and documentation. Informants in this study is the head unit for the education of Kecamatan Tembalang, headmaster, teachers and parents. The result showed obstacles in the implementation of the program, there are several agencies that still graduated from senior high school. Professional teachers should possess the minimum academic qualifications Bachelor's degree (S-1) or four diploma (D-IV), master the competencies (pedagogy, professional, social and personality). The condition of facilities and infrastructures are less supportive in maximizing the PAUD program. Unit for the education of Kecamatan Tembalang lack Human Resources especially for the position of overseer of PAUD. Recommendations for improving the PAUD's program in tembalang is the need for competence development training to educators education. Mapping the needs of institutions of PAUD objectively. Provide incentives and ease to the teacher to proceed to a higher level. The addition of human resources for the position of overseer.